Integrated Vehicle Health Management - Business Case Theory and Practice. - Jennions, Ian K. (Integrated Vehicle Health Management Ser., 2012)
Following the best seller, Integrated Vehicle Health Management: Perspectives on an Emerging Field, the new title Integrated Vehicle Health Management: Business Case Theory and Practice takes the subject to the next level. This time it addresses the commercial justification for the adoption of a new modus operandi in asset health management, and its impact on business strategy and servitization of technology. Edited by Dr. Ian Jennions, Director of the IVHM Center at Cranfield University in the U.K., the book tackles the most important questions on the transformation of business from selling a.